DOCUMENTARY TELEVISION FILM - A N Shirobokov; K B Baryshnikov (RUDN Journal of Studies in Literature and Journalism, 2017)
The article covers the special report as a TV genre. The authors discuss its origin, history and current role on television. The development of this genre is linked to the works of such local journalists as A.G. Malkina, I.K. Belyaeva, M.E. Goldovskaya, V. Lisakovich and film director S. Govorukhin. “Genre diffusion” as the special report basis has evolved from the efforts to project huge historical events taking place in the 90-s of the 20-th century on movie and television screens. These events simply didn’t fit into the timeframe and theme limits of a conventional TV report. The scale and importance of these events demanded a search for new forms of presenting the material that would maintain the suspense of reporting and enable to fully examine and analyze the events. The article provides the analysis of movie and television films made in the 90-s of the last century